Penguatan Kelembagaan Badan Usaha Milik Desa (BUMDes) Sumber Arto Desa Kenteng - Susilowati, Nurdian; Anisykurlillah, Indah; Asrodin, Mukhammad; Mahmud, Amir; Rahmawati, Eka; Ananda, Delya Saski (Universitas Negeri Semarang, 2021)
Community service activities aim to identify the completeness of the institutional elements of BUMDes Sumber Arto Kenteng Village. The service method used is the socialization of BUMDes strengthening following government regulation number 11 of 2021 and the procedures, requirements, and registration of BUMDes names. The target of the activity is the BUMDes management and the village secretary. Activities are carried out virtually using zoom meetings, and the continuation of activities is carried out through communication using Whatsapp. The service results showed that participants began to understand the mechanism for proposing BUMDes to legal entities as the main element in strengthening BUMDes institutions. BUMDes already has an organizational structure but does not yet have standard operating procedures for business implementation. These include strategies for team member payroll, cash receipts, cash disbursements, sales, and purchases. Team member turnover is also relatively high, making it challenging to perform the functions of the supervisory and accounting departments. Therefore, it is necessary to create and set standard operating procedures. These operational standards are legalized in village consultation meetings (musrenbangdes).